2008
DOI: 10.1103/physrevlett.100.035003
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Large Arrays of Plasma Filaments in Air Breakdown by 1.5-MW 110-GHz Gyrotron Pulses

Abstract: We report the observation of two-dimensional plasma filamentary arrays with more than 100 elements generated during breakdown of air at atmospheric pressure by a focused Gaussian beam from a 1.5-MW, 110-GHz gyrotron operating in 3-s pulses. Each element is a plasma filament elongated in the electric field direction and regularly spaced about one-quarter wavelength apart in the plane perpendicular to the electric field. The development of the array is explained as a result of diffraction of the beam around the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
99
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 156 publications
(110 citation statements)
references
References 7 publications
10
99
0
1
Order By: Relevance
“…The temporal behavior of the breakdown process is also reported. The present results are an extension of our previous study, 6 in which we reported the first observation of a regular two-dimensional array of filaments in atmospheric air breakdown at 110 GHz. These filaments are qualitatively different from, and should not be confused with, the well-known filaments observed in laser breakdown.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…The temporal behavior of the breakdown process is also reported. The present results are an extension of our previous study, 6 in which we reported the first observation of a regular two-dimensional array of filaments in atmospheric air breakdown at 110 GHz. These filaments are qualitatively different from, and should not be confused with, the well-known filaments observed in laser breakdown.…”
Section: Introductionsupporting
confidence: 71%
“…Third, and most importantly, the series of fast camera images have experimentally confirmed that the sequential development of the plasma filamentary array is indeed occurring as we hypothesized in our purely electromagnetic wave model described in Ref. 6. That model predicts that after the formation of a first filament, subsequent filaments will be created upstream of that filament, with a spacing of about a quarter wavelength.…”
Section: Phys Plasmas 16 055702 ͑2009͒mentioning
confidence: 69%
See 3 more Smart Citations